EFFECT OF COGNITIVE BEHAVIOURAL THERAPY ON MANAGING POST TRAUMATIC EXPERIENCE AMONG WIDOWS IN IKWERRE LOCAL GOVERNMENT AREA OF RIVERS STATE - NWANKWO, Patience N. (Journal of Professional Counselling, 2025)
This study examines the effect of Cognitive Behavioral Therapy (CBT) on post-traumatic experiences and emotional well-being among widows in Ikwerre Local Government Area of Rivers State, Nigeria. Using a quasi-experimental design, the study involved 240 widows divided into an experimental group that received CBT and a control group that did not receive any specific intervention. The Post-Traumatic Stress Disorder Checklist – Civilian Version (PCL-C) and the Positive and Negative Affect Schedule (PANAS) were used to measure posttraumatic symptoms and emotional well-being, respectively. The instruments undergo face validation by a panel of experts in psychology and trauma studies, who reviewed the items for clarity and appropriateness for the study population. Reliability was ensured by conducting a pilot study and the Cronbach's alpha reliability coefficient was calculated with a value of 0.87. Data were analyzed using descriptive statistics, paired t-tests, and ANCOVA. Results showed that CBT significantly reduced post-traumatic stress symptoms and improved emotional wellbeing in the experimental group, particularly among widows who had been widowed for less than five years. The findings suggest that early intervention through CBT can be highly effective in mitigating trauma-related symptoms and enhancing emotional health in widows. It was also found that the duration of widowhood moderated the effectiveness of the therapy. Based on the results, it is recommended that early intervention programs for widows be prioritized, and that alternative therapeutic approaches be considered for widows experiencing long-term bereavement.